Lean Body Mass and Self-Perceived Body Image among Youth in the United Arab Emirates: Muscle and Body Image among Youth in UAE - Hasan, Hayder A.; Radwan , Hadia; Al Majid , Fatma; Al Hilo, Fatma; Mohammed , Rahaf; Al Shaikh , Shooq; Al Qassim, Asma i; Aboubaker , Hajer; Karavetian, Mirey (Acta Biomedica Atenei Parmensis, 2022)
Background and Aim: Lean body mass may be a promising tool to screen body image disorders. This study aim was to explore the relationships between fat free mass index (FFM-I) on self-perceived body image and shape among university students in the United Arab Emirates.Methods: Cross-sectional study, using questionnaires to evaluate demographics, body figure, shape and image dissatisfaction; in addition to anthropometrics like BMI and FFM-I. Accordingly, participants were categorized into adequate muscle mass (AMM) and low muscle mass (LMM) individuals.Results: A total of 402 participants (50.4% females) aged between 18 and 25 years, were recruited. Almost third (33.8%) of the participants were overweight/obese, 81% had AMM; 48.5% and 76.3% of them were concerned about their body shape and image, respectively; 55.2% desired to be thinner. Males (M) had significantly higher BMI and body fat compared to females (F). Subjects with LMM, irrespective of sex, were underweight (49% F; 40.7% M), desired to be heavier (44.9% F; 74.1% M) and they had a lower agreement in their perceived BMI versus actual (k=0.024; poor) compared with those with AMM (k=0.408; fair); and in general males had a better agreement between their perceived and actual BMI compared to females (0.432, moderate vs. 0.308, fair).Conclusions :Our results conclude that female sex and LMM were associated with higher body image and shape dissatisfaction; thus, highlighting the importance of increasing awareness among youth to assess body composition and engage in muscle mass building activities as an effective step towards improving body image perception. (www.actabiomedica.it)